Tanah Grant Sultan Melayu Deli menurut Teori Positivistik - Rafiqi Rafiqi (Jurnal Ilmiah Penegakan Hukum, 2019)
"Grant Sultan" land certificate is not the basis of rights. The certificate only explained that the land was Grant Sultan's previous right. The Sultan Grant Certificate is a guide for the National Land Agency to see the basis for land ownership. In accordance with the Basic Agrarian Law (UUPA) No. 5/1960, land that is certified by Grant Sultan will be converted to land, either direct or indirect conversion, further consideration and assessment needs to be done. From the background of this writing the problem is formulated How Legal Certainty Land Registration holders of Grant Sultan Land in Deli Malay Customary Community, how Grant Sultan Land in Deli Malay society is seen from Positivistic Theory The research method used in this writing is a regulatory approach and concept. Legal Certainty Land Registration of Grant Sultan Land holders in the Deli Malay Customary community if seen from the positivistic school of thought that Grant Sultan's land must be registered by Grant Sultan holders to ensure legal certainty. Grant Sultan's land in the Deli Malay community is seen from the Positivistic Theory. According to the Pound the law is a Social Engineering conflict with interests compared to the others. From positivistic theory Grant holders must immediately register Grant land in accordance with Government Regulation No. 24 of 1997 concerning Land Registration.